AB1353 How much temperature can truly impact on raynaud's phenomenon secondary to systemic sclerosis?. (12th June 2018) - Schioppo, T.; Orenti, A.; Boracchi, P.; De Lucia, O.; Murgo, A.; Ingegnoli, F.
Abstract : Background: Raynaud's phenomenon (RP) is considered a prominent feature of systemic sclerosis (SSc). 1 SSc-RP is related to considerable disease-related morbidity including pain, impaired hand function, reduced social participation, body image dissatisfaction, increased reliance on others and reduced quality of life. 2 In most cases RP is triggered by low environmental temperature or sudden variation of it. According to EULAR recommendations, intravenous (IV) iloprost (ILO) should be used to control severe RP, after oral therapy failure. 3 Unfortunately no validated IV ILO regimens have been so far published. Objectives: Aim of our study was to estimate the impact of environmental temperature on RP in patients with SSc treated with two different IV ILO regimens and in patients not treated with IV ILO. Methods: We conducted a monocentric, prospective, pragmatic and non-randomised study, after the local ethical committee approval, between September 2016 and February 2017. In the present study, we enrolled all consecutive SSc patients not requiring therapy with IV ILO (group A), or requiring therapy with IV ILO once monthly (group B) or therapy with IV ILO for 5 consecutive days every 3 months (group C). RP severity was evaluated through a visual analogue scale (VAS) from 0 to 10. Group A and C patients were evaluated at baseline and after 3 months. Group B were evaluated at every infusion for 3 months. Environmental temperature for each patient was calculated as the mean temperature during the week before the evaluation in the place of residence (data supplied by Meteo Operations Italia (MOPI) SrL – Centro Epson Meteo). Moreover for each participations demographic and disease characteristics were collected at baseline. Results: 96 patients were enrolled in the study: 52 in group A, 24 in group B, and 20 in group C. Of these 35, 21 and 16 respectively completed the study. RP VAS was related to the average temperature observed the week before the evaluation at place of residence. In group A, VAS RP decreases of −0.072 for a growth of one grade of the temperature (IC 95%: −0.206–0.061, p-value=0.297). In group B, VAS RP decreases of −0.278 for a growth of one grade of the temperature (IC 95%: −0.397 – −0.160, p-value<0.001). In group C, VAS RP decreases of −0.053 for a growth of one grade of temperature (IC 95%: −0.201–0.095, p-value=0.483). Conclusions: RP severity, as assessed by VAS, showed a correlation with the environmental temperature. This information could support the seasonal administration of IV ILO only during the coolest periods of the year. References: [1] Park JS, et al. Application of the 2013 ACR/EULAR classification criteria for systemic sclerosis to patients with Raynaud's phenomenon. 2015. [2] Frantz C, et al. Impaired quality of life in systemic sclerosis and patient perception of the disease: a large international survey. 2016. [3] Kowal-Bielecka, et al. Update of EULAR recommendations for the treatment of systemic sclerosis. 2017. Acknowledgements: We thank Meteo Operations Italia (MOPI) SrL – Centro Epson Meteo for providing temperature data. Disclosure of Interest: None declared